Analisis Pergeseran Budaya Kawin Tangkap Terhadap Perempuan Dalam Pemikiran Legal Feminist Di Kabupaten Sumba Tengah - Fortuna Umbu Laiya, Andraviani; Kopong Medan, Karolus; Sinurat, Aksi (UNES Law Review, 2024)
The culture of capture marriage in Central Sumba Regency has experienced a shift in cultural values that has resulted in violence against women, triggering debates between customary law and Indonesian positive law. This study aims to describe the essence of the culture of catch marriage for women in Central Sumba Regency and its compatibility with Positive Law and to elaborate on the shift in the culture of catch marriage for women in Central Sumba Regency in Legal Feminist thinking. The research method used is empirical legal research which obtains data from primary data or data obtained directly from the community and library legal sources. The results of the study show that the practice of catch marriage is no longer in line with the principles of the Indonesian State which ratified the Human Rights Law, because this practice indicates various oppression against women specifically in the process of arrest and detention. Using feminist legal theory, from the legal text analysis approach, it is found that the weaknesses of customary law in Central Sumba are patriarchal and communal, while the legal text of the Sexual Violence Crime Law has weaknesses in the unavailability of implementing regulations and there is a legal vacuum in the local government of Central Sumba Regency regarding arrest marriages. In the approach to legal application, cases of capture marriage are dominantly resolved by custom, due to family relations and the attachment of capture marriage to the culture of the indigenous people of Central Sumba. The novelty in this research is to describe the essence of culture and the reality of a shift in the culture of capture marriage in Central Sumba Regency, which is analyzed through a legal feminist theory approach to its handling. This research is only limited to the culture of capture marriage that occurs in Central Sumba Regency in a feminist legal approach.